2006
DOI: 10.1086/500272
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Linkage Scan of 409 European-Ancestry and African American Families with Schizophrenia: Suggestive Evidence of Linkage at 8p23.3-p21.2 and 11p13.1-q14.1 in the Combined Sample

Abstract: We report the clinical characteristics of a schizophrenia sample of 409 pedigrees--263 of European ancestry (EA) and 146 of African American ancestry (AA)--together with the results of a genome scan (with a simple tandem repeat polymorphism interval of 9 cM) and follow-up fine mapping. A family was required to have a proband with schizophrenia (SZ) and one or more siblings of the proband with SZ or schizoaffective disorder. Linkage analyses included 403 independent full-sibling affected sibling pairs (ASPs) (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
112
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 72 publications
6
112
1
Order By: Relevance
“…While this locus has not been previously reported in linkage analyses of BP with psychosis, it has been implicated in a scan of BP 16 and in another of schizophrenia. 41 Additionally, this region is < 18 Mb away from BDNF, which has been associated with both BP and schizophrenia. 42 Given the low resolution of the linkage method, it is hard to determine whether the current finding represents the same locus or not.…”
Section: Discussionmentioning
confidence: 99%
“…While this locus has not been previously reported in linkage analyses of BP with psychosis, it has been implicated in a scan of BP 16 and in another of schizophrenia. 41 Additionally, this region is < 18 Mb away from BDNF, which has been associated with both BP and schizophrenia. 42 Given the low resolution of the linkage method, it is hard to determine whether the current finding represents the same locus or not.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-five of these families were part of a larger molecular genetic study of schizophrenia, the NIMH GI SZ MGS1, a collaboration of 10 centers (nine US and one Australian). 24 Participants were recruited from clinical networks and advocacy groups such as Schizophrenia Fellowship. Individuals (18 years or older) were interviewed by trained research clinicians using the Diagnostic Interview for Genetic Studies 2.0 (DIGS), 25 a semistructured interview specifically constructed for the assessment of psychotic and major mood disorders.…”
Section: Replication Subjectsmentioning
confidence: 99%
“…Recent linkage studies have suggested that a susceptibility locus for BPD exists on chromosome 8p21-22 (Cichon et al, 2001;Ophoff et al, 2002;Park et al, 2004;Cheng et al, 2006). Interestingly, numerous linkage studies in schizophrenia (SZ) report a susceptibility locus on 8p21 (Pulver et al, 1995(Pulver et al, , 2000Kendler et al, 1996;Straub et al, 1996;Blouin et al, 1998;Brzustowicz et al, 1999;Gurling et al, 2001;Stefansson et al, 2002;Lewis et al, 2003;Suarez et al, 2006) and a candidate gene from this region, neuregulin 1 (NRG1), was associated with SZ (Stefansson et al, 2002(Stefansson et al, , 2003Williams et al, 2003;Yang et al, 2003;Corvin et al, 2004;Li et al, 2004;Tang et al, 2004;Petryshen et al, 2005); however, NRG1 is located about 10-15 cM away from the major linkage peaks and others could not confirm an association between the NRG1 gene and SZ (Bakker et al, 2004;Hong et al, 2004;Iwata et al, 2004;Thiselton et al, 2004;Duan et al, 2005;Liu et al, 2005). The report of multiple linkage studies in BPD and SZ supports the hypothesis of a shared susceptibility locus for BPD and SZ on 8p (Berrettini, 2003(Berrettini, , 2004.…”
Section: Introductionmentioning
confidence: 99%